"There's no disenfranchisement when you're sitting in that room": Evaluating a South Australian loss and grief support group for foster and kinship carers. (July 2022) - Riggs, Damien W.; Allain, Tandanya; Browne, Liz; Endacott, Fiona; Quince, Amanda
Highlights: Unplanned placement terminations impact on sense of parental identity. Formal support groups can help carers to see the contribution they have made to a child's life. Practices of memorialisation in support groups enable carers to process loss and grief. A restorative approach can help to address ambiguous loss following placement termination. Abstract: For foster or kinship carers who provide long-term care to children who are unable to live with their birth parents, a strong bond is often formed. Yet despite the best intentions of all parties, in some cases placements may be terminated, often leaving foster or kinship carers dealing with considerable loss and grief. This paper reports on the evaluation of a South Australian support group tailored to the needs of foster and kinship carers experiencing loss and grief following an unplanned placement termination. The paper provides an overview of the group, and reports on a thematic analysis of eight interviews with group attendees. The findings in regard to factors leading to placement termination and the impact of placement termination on foster families echo previous research on the topic. The findings with regard to the benefits of group attendance emphasise the utility of its restorative practices approach, highlighting that the group created a space in which participants could acknowledge what had been achieved for the child, take perspective about their role as a foster parent, recognise the attachment they shared with the child, and the use of group activities gave presence to the grief and helped participants to honour their relationship to the child. The paper concludes with recommendations for future research and highlights the benefits of a restorative practice approach to addressing disenfranchised grief and ambiguous loss among foster and kinship carers who have experienced an unplanned placement termination.